Effect of ultrasonic pretreatment on gaharu essential oil using supercritical carbon dioxide extraction: article - Idzahar, Kamilia; Che Radzi, Nurhaslina (2018)
Gaharu or commonly known as Agarwood, is a resinous heartwood in trees of Aquilaria genus and Thymelaeaceae family which is widely known as one of the most highly precious fragrant woods as it producse essential oil that is economically significant. However, conventional extraction method without the pretreatment produced small oil yield. Therefore, this experiment was carried out to determine the effect of ultrasonic pretreatment on gaharu essential oil using supercritical carbon dioxide extraction. Ultrasonic pretreatment was done at 30°C, 40°C and 50°C for 1 hr. The extraction was carried out at temperature of 40°C, 45°C, 50°C and pressure of 3000 psi, 4000 psi and 5000 psi. Gaharu from the species of Aquilaria Malaccensis was used in this experiment. The optimum temperature and pressure for the extraction was 50°C and 5000 psi respectively at which the highest oil yield was obtained (0.1867%) for the pretreated gaharu. The chemical compounds present in the essential oil were analyzed by using Gas Chromatograph Mass Spectrometry (GC-MS).